2021
DOI: 10.1002/psc.3361
|View full text |Cite
|
Sign up to set email alerts
|

Labeling and receptor affinity of an ultra‐short somatostatin analogue Thz‐Phe‐D‐Trp‐Lys‐Thr‐DOTA

Abstract: Somatostatin analogues play an important role in the therapy of neuroendocrine tumors by binding to somatostatin receptors on the surface of cancer cells. In this work, we analyze the receptor-binding affinity and in vitro stability of a novel ultra-short somatostatin analogue Thz-Phe-D-Trp-Lys-Thr-DOTA (DOTA-P4). This conjugate is successfully radiolabeled with 44 Sc, 90 Y, 152 Eu, and 207 Bi, characterized and validated by thin layer and high-performance liquid chromatography. The optimum conditions for M-DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…DOTA chelating agent was chosen due to its excellent chelating properties toward both 68 Ga (PET/CT diagnostics) and 177 Lu (radionuclide therapy) radioisotopes and its numerous examples of successful biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…DOTA chelating agent was chosen due to its excellent chelating properties toward both 68 Ga (PET/CT diagnostics) and 177 Lu (radionuclide therapy) radioisotopes and its numerous examples of successful biomedical applications. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fedotova et al reported the synthesis of an ultra-short somatostatin analogue Thz-Phe-D-Trp-Lys-Thr-DOTA (DOTA-P4) labelled with trivalent cations including 44 Sc. 132 The precursor of DOTA (DO3A, 1.1 equiv.) was linked to the chloroacetyl derivative of the peptide (1 equiv.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%